(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2024)
Purpose – This paper aims to: (1) examine the effect of social media advertisement and influencers on Compulsive buying, (2) investigate the role of materialism as a mediator and narcissism as a moderator on the relationship between social media advertisement and influencers on Compulsive Buying. Design/methodology/approach – The study is based on 300 responses. Data of the responses was used for statistical analysis and hypothesis testing. The study uses Structural Equation Modelling (SEM) to test all hypotheses. Findings – The study revealed insignificant relationships between social media advertisements and influencers, and compulsive buying. The findings provided evidence that materialism mediates the relationship between social media advertisements and compulsive buying. In contrast, materialism does not mediate the relationship between social media influencers and compulsive buying. The study failed to reveal a moderating role of narcissism on the relationship between materialism and compulsive buying. Research implications – Recommendations for marketing managers, scholars, and policymakers have been given adopting the marketing orientation that puts the consumers’ satisfaction of needs and wants first, based on the researchers’ faith that compulsive buying is not a virtue for consumers by all means. Originality/value – This paper investigates one of the most pressing issues regarding consumer behaviour in social media, consumer traits, and compulsive buying.